Quality of Life in Cervical Cancer Patients who Underwent Desobstruction Procedures (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2020)
Objective: Obstructive uropathy is a common condition in hospitalized cervical cancer patients. Many patients underwent surgical procedures to improve their QoL. This study was aimed to compare the quality of life (QoL) and Survival Rate in cervical cancer with obstructive uropathy pre and post operative in the Urology Department at Saiful Anwar General Hospital from July 2016 to August 2017. Materia and Method: 75 patients with obstructive uropathy in cervical cancer underwent desobstruction procedures. Inclusion criteria was patient with bilateral or unilateral hydronephrosis. Exclusion criteria where patients who loss of follow up. QoL was assessed using WHO QoL-BREF which has 4 domains; (I:physical health, II: physiologic health, III: social relationships and IV: environmental health). The results before and after procedure were compared using Mann Whitney in a prospective manner. Result: From 75 patients, 64 cases had bilateral obstruction and 11 cases had unilateral obstruction. 43 (57%) patients underwent desobstruction procedures as follows: retrograde DJ stent in 31 patients; internal ureteral DJ stent in 2 patients; ureterocutaneostomy in 9 patients; percutaneous nephrostomy in 1 patient. There are 32 patients without desobstruction procedures. Result showed that patient’s QoL in the domain I to IV were significantly decreased in 6 months and 1 year follow up period. There was no significant difference of QoL between all surgical procedures (p=0.872). The survival rate between retrograde diversions and open diversions were not significantly different (p=1.356). Concluison: Desobstructions procedure did not improve QoL in cervical cancer patients with obstructive uropathy at 6 months and one year follow up period.